Mobile application-based guidelines to enhance patient care and provider education in trauma and acute care surgery. Issue 1 (23rd July 2020) - Hakes, Nicholas A; Kethman, William C; Spain, David; Nassar, Aussama K
Abstract : Introduction: Providing up-to-date, universally accessible care guidelines and education within a quaternary care center is challenging. At our institution, trauma and acute care surgery guidelines have historically been published using a paper-based format. Mobile application-based guidelines were developed to address the shortcomings of paper-based guidelines. Methods: We assessed the utility, usability, and satisfaction of healthcare providers towards paper-based versus mobile application-based guidelines. A survey was administered to providers within the emergency department and intensive care unit. Results: Fifty of 137 providers responded (36.5% response rate). Nearly half (47.4%, 9 of 19) of those who received a copy of the paper-based guidelines lost the guidelines at least once. Regarding usage of the mobile application-based guidelines, 92.6% (25 of 27) were aware of the application; 92.6% (25 of 27) considered the application comprehensive, 85.2% (23 of 27) thought the application was organized, and 66.7% (18 of 27) thought the application was easy to use. Additionally, 88.9% (24 of 27) found the application moderately, very, or extremely helpful and 85.2% (23 of 27) judged the application moderately, very, or extremely necessary. Overall, 88.9% (24 of 27) were satisfied with the application and indicated likeliness to recommend to a colleague. Seventeen of 27 (63.0%) agreed or strongly agreed that the application improved their provision of trauma and acute care. Conclusion: This survey demonstrates positive usability, utility, and satisfaction among trauma healthcare providers with the mobile application-based guidelines. Additionally, this quality improvement initiative highlights the importance of having comprehensive, organized, and easy-to-use trauma and acute care surgery guidelines and targeted educational materials available on demand. The successful transition from paper to mobile application-based guidelines serves as a model for other institutions to modernize and improve patient care and provider education. Level of evidence: IV.